Screening for Anti-HMGCR Antibodies in a Large Single Myositis Center Reveals Infrequent Exposure to Statins and Diversiform Presentation of the Disease - Szczesny, Piotr; Barsotti, Simone; Nennesmo, Inger; Danielsson, Olof; Dastmalchi, Maryam (Frontiers in Immunology, 2022)
Background The objective of this study is to assess the frequency of autoantibodies against 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase (HMGCR) in a single center myositis cohort and to analyze associations with statin exposure, clinical features, and outcome of disease course. Methods A total of 312 patients with idiopathic inflammatory myopathies (IIMs) followed at the rheumatology clinic, Karolinska University Hospital, were identified in the Euromyositis registry between 1988 and 2014 and were classified according to the 2017 European Alliance of Associations for Rheumatology/American College of Rheumatology (EULAR/ACR) criteria. Available serum samples were analyzed for anti-HMGCR autoantibodies by ELISA. Positive sera were confirmed by immunoprecipitation. Clinical data were extracted from Euromyositis registry and medical records. Muscle samples were examined by two pathologists blinded to the subjects’ autoantibody status. Results Of 312 patients, 13 (4.3%) were positive for anti-HMGCR. Two of the 13 (15%) anti-HMGCR–positive patients had histories of statin use versus 12 (4.2%) in the anti-HMGCR–negative group. In the anti-HMGCR–positive group, five (38%) had a clinical phenotype compatible with dermatomyositis. Muscle biopsies of patients with HMGCR autoantibodies showed findings consistent with immune-mediated necrotizing myopathy in all cases except for one. Five (38%) patients required treatment with intravenous immunoglobulin compared to seven (2.3%) without this antibody. At the last visit, seven patients had chronic, active disease course, and five of 13 patients were in remission, including three without treatment. Conclusions Patients with IIM related to anti-HMGCR autoantibodies may present with a wide range of symptoms, more than previously anticipated. When a broad approach to screening for these antibodies is applied, only a minority of patients was found to have previous statin exposure. The results of this study justify the addition of anti-HMGCR autoantibodies to routine diagnostic procedures in patients with myositis.